Famine and food security in Ethiopia: lessons for Africa - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1996)
Famine and food security in Ethiopia: lessons for Africa by Patrick Webb and Joachim von Braun 1994 158pp